Interaction of Eu(III) with mammalian cells: Cytotoxicity, uptake, and speciation as a function of Eu(III) concentration and nutrient composition. Issue 7 (October 2015) - Sachs, Susanne; Heller, Anne; Weiss, Stephan; Bok, Frank; Bernhard, Gert
Graphical abstract